Intentional mind-wandering as intentional omission: the surrealist method (2021)
ABSTRACT: Mind-wandering seems to be paradigmatically unintentional. However, experimental fndings have yielded the paradoxical result that mind-wandering can also be intentional. In this paper, we frst present the paradox of intentional mind-wandering and then explain intentional mind-wandering as the intentional omission to control one’s own thoughts. Finally, we present the surrealist method for artistic production to illustrate how intentional omission of control over thoughts can be deployed towards creative endeavors.